Pusat Pendidikan Islam Berbasis Masjid - Yusi Srihartini; Andri Yuningsih; Suwanggi Leman (At-Tadris: Journal of Islamic Education, 2025)
Mosques and Islamic education are two parts that cannot be separated from each other. The two always go hand in hand in the long journey of the dynamics of Islamic education. The purpose of this article is to describe the concept of empowering mosques as centers of Islamic education and optimizing the potential of mosques as centers of Islamic education. By answering the various questions above through in-depth analysis and interpretation, it is hoped that this article can become a reference for the development of mosque empowerment and Islamic education in general. This article uses a qualitative research approach (library research). The analysis uses the Miles and Huberman interaction model. This article shows that the endorsement of mosques as centers of Islamic education reflects the function of mosques other than praying five times a day in congregation. Here it is necessary to mobilize the ta'lim assembly, empower youth, organize various training and seminars, make the mosque a center of knowledge, increase cooperation, empower poor communities and encourage mosque independence. Optimizing the potential of mosques as centers of Islamic education must be continued by improving mosque management, optimizing the religious sector, youth sector, social sector, cultural sector and economic sector. To empower mosques in this way, the Islamic Education Center, with various concepts explained. Good management of mosques, as well as optimizing various areas within the mosque, is not limited to just words but there is also a level of actual action for the welfare of the mosque and its implementation turns the mosque into a center. Islamic education.